2020
DOI: 10.1073/pnas.1919403117
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Impaired lipid metabolism by age-dependent DNA methylation alterations accelerates aging

Abstract: Epigenetic alterations and metabolic dysfunction are two hallmarks of aging. However, the mechanism of how their interaction regulates aging, particularly in mammals, remains largely unknown. Here we show ELOVL fatty acid elongase 2 (Elovl2), a gene whose epigenetic alterations are most highly correlated with age prediction, contributes to aging by regulating lipid metabolism. Impaired Elovl2 function disturbs lipid synthesis with increased endoplasmic reticulum stress and mitochondrial dysfunction, leading to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…For the first and second points, previous to the mating, the role of the FA in the sperm quality has been the most described [ 34 ]. Little information is available with regard to the effect of dietary FA and epigenetic changes in offspring using ruminants such as animal models [ 35 ]. Nevertheless, for mammals, a few pieces of evidence have described the role of PUFA in the spermatozoa epigenome, in particular, DNA oxidation, DNA methylation, and gene expression associated with lipid metabolism [ 30 ].…”
Section: Fatty Acid Supplementation Before and During The Conceptimentioning
confidence: 99%
“…For the first and second points, previous to the mating, the role of the FA in the sperm quality has been the most described [ 34 ]. Little information is available with regard to the effect of dietary FA and epigenetic changes in offspring using ruminants such as animal models [ 35 ]. Nevertheless, for mammals, a few pieces of evidence have described the role of PUFA in the spermatozoa epigenome, in particular, DNA oxidation, DNA methylation, and gene expression associated with lipid metabolism [ 30 ].…”
Section: Fatty Acid Supplementation Before and During The Conceptimentioning
confidence: 99%
“…Increasing methylation of Elovl2 has recently been reported to be a crucial driver of aging by inducing a stress response in the endoplasmic reticulum and promoting mitochondrial dysfunction [ 6 ]. In some degenerative diseases, mitochondrial DNA and genes encoding the enzymes responsible for mitochondrial biogenesis, such as Mfn2 in diabetes, are hypermethylated and compromise the electron transport chain [ 72 ].…”
Section: Mechanisms Of Aging Induced By Dna Methylationmentioning
confidence: 99%
“…These modifications alter the extent to which DNA is wrapped around histones and the availability of genes within the DNA to be activated. Recently, numerous studies have emphasized the unique role of DNA methylation in aging [ 6 , 7 ]. In addition to its effects on the aging process, a function shared by other epigenomic regulators, DNA methylation can also predict aging status.…”
Section: Introductionmentioning
confidence: 99%
“…56 Other studies have identified several genes that are highly correlated with DNA methylation age including ELOVL fatty acid elongase 2 ( ELOVL2 ) and H3K36 methyltransferase ( NSD1 ). 127,128 ELOVL2 is the master controller of poly-unsaturated fatty acid synthesis and was most significantly related to DNA methylation age. Although the relationship of ELOVL2 to DNA methylation clocks has been well documented, the mechanism underlying how age-related ELOVL2 methylation contributes to aging is unknown.…”
Section: Dnam Age Acceleration and Genetic Factorsmentioning
confidence: 99%
“…A recent report documented a dramatic increase in ELOVL2 methylation that was accompanied by downregulation of ELOVL2 expression levels in aged human fibroblasts. 128 Moreover, dysfunction of the Elovl2 protein interferes with lipid metabolism and synthesis, increasing endoplasmic reticulum stress and mitochondrial dysfunction, which are associated with accelerated aging. A recent gene screening study found that DNA methylation clocks tick more quickly in the blood of patients with Sotos syndrome, a familial developmental disorder caused by inactivation mutations of NSD1.…”
Section: Dnam Age Acceleration and Genetic Factorsmentioning
confidence: 99%